Організація роботи органів земського самоврядування по виробництву й популяризації керамічних вогнетривких матеріалів у Полтавській губернії на прикладі Роменського повіту (початок ХХ ст.) - Белько, О.О. (Сіверщина в історії України, 2021)
У статті йдеться про реалізацію заходів Полтавського губернського земства по виготовленню, збереженню й популяризації вогнетривких матеріалів у Роменському повіті. Досліджуються земські ініціативи з розповсюдження глиняної черепиці на Полтавщині через мережу складів вогнетривких матеріалів. Аналізуються етапи вирішення проблем, що постали перед органами земського самоврядування, від організаційних питань до забезпечення населення вогнетривкою продукцією. Наводяться приклади вирішення кадрових питань, які були на часі, а саме: як Полтавське губернське земство реалізовувало свої плани з оснащення складів, розширення їхніх площ та матеріально-технічного забезпечення. Подаються відомості про ставлення місцевого населення до керамічних вогнетривких матеріалів та застосування їх в рамках земської програми вогнетривкого будівництва. The activity of zemstvo self-government bodies is increasingly attracting the attention of scientists and local historians - all of whom are not indifferent to the historical past and future of the Ukrainian state. A valuable help for contemporaries can be a package of zemstvo directive documents and study the experience of their implementation, how to raise living standards, preserve and increase the cultural traditions of the region. Measures of the Poltava provincial zemstvo on refractory construction at the turn of the XIX–XX centuries were carried out purposefully. The experience of Poltava Provincial Zemstvo in determining the priority socio-economic activities and their systematic implementation needs to be studied. The review is devoted to the implementation of measures of the Poltava provincial zemstvo to open zemstvo warehouses of refractory materials in Romny district. Zemstvo initiatives for the distribution of clay tiles in Poltava region through a network of warehouses of refractory materials are being studied. Examples of resolving personnel issues that arose in time and how the Poltava Provincial Zemstvo implemented its plans to equip warehouses, expand their area and logistics are given. Information is provided on the expectations and attitudes of the local population to the warehouses of refractory materials and their use in the framework of the Zemstvo program of refractory construction. Analyzing the above in the activities of the Poltava Provincial Zemstvo, the provincial administration, there is a clear planning of work, efficiency in action, relevance and relevance of decisions, deep awareness of the case on the ground, purposefulness in achieving the goal. Through a system of administrative and organizational measures, the zemstvos actively implemented the state social policy to protect the population in emergencies by opening both permanent and temporary warehouses of refractory materials in accordance with the approved plans.